Development of renal fibrosis in patients with chronic kidney disease: Mechanisms, biomarkers, and clinical implications - Denova, L. (Ukrainian Journal of Nephrology and Dialysis, 2023)
CKD is a global health concern with significant implications for patients’ well-being, morbidity, and mortality. The underlying mechanism of CKD development often involves progressive interstitial fibrosis. Understanding the processes and factors influencing fibrogenesis is crucial. This review aims to analyze recent literature on the pathophysiological mechanisms, early diagnosis, prevention, and treatment of renal fibrosis in CKD patients. It explores various aspects of kidney fibrogenesis, highlighting key pathogenic factors and signaling pathways that warrant further investigation. The review emphasizes the potential of urinary uromodulin (uUmod) as a biomarker for early renal fibrosis diagnosis and delves into the role of anemia, kidney hypoxia, vitamin D, and unique aspects of fibrosis development in diabetic kidney disease patients. Furthermore, it underscores the importance of inhibiting the renin-angiotensin-aldosterone system (RAAS) as a strategy for fibrosis prevention and attenuation.